Soil Physicochemical Status and Nutrient Management for Paddy Soils in the Lower Central Plain of Thailand after the Flood Disaster in 2011 - Intorpetch, Benjaporn; Wisawapipat, Worachart; Arunlertaree, Chumlong; Teartisup, Piyakarn (Environment and Natural Resources Journal, 2014)
The soil fertility status were evaluated for 29 paddy soils in Phra Nakhon, Si Ayutthaya and Pathum Thani provinces, Thailand that had been affected by the flood disaster in 2011. The chemical fertility status of the soils in the flood affected areas was medium, which is relatively superior to the pre-flood condition. The available potassium in most soils was slightly larger (mean = 220 mg kg-1) than the values previously reported on these soils (mean = 188 mg kg-1). However, mean values of available phosphorus for most soils were rather small (7.5 mg kg-1), indicating a loss of phosphorus fertility and those farmers in the flood affected areas needed to apply additional phosphorus fertilizer in order to achieve satisfactory crop yields. Liming should also be used to minimize potential Al/metals toxicity and correct imbalances of plant nutrients. Several plant nutrients (NPK) and organic materials need to be regularly applied to maintain soil fertility levels at optimum values.